Referrals to chaplains: The role of religion and spirituality in healthcare settings - Galek, Kathleen (Mental health, religion & culture, 2007)
Given the increasing importance of understanding how healthcare workers interact with the principal person designated to meet patients’ spiritual needs— the chaplain— the current study provides an inter-disciplinary perspective of the role of chaplains (and spirituality) in patients’ emotional, physical, and spiritual health. The study surveyed a randomly selected national sample of hospital directors in four disciplines: medicine (n = 278), nursing (n = 230), social services (n = 229), and pastoral care (n = 470). Participants rated the importance of referring patients to chaplains for four different areas: pain/depression, anxiety/anger, treatment issues, and loss/death/meaning. Results revealed significant differences in referral patterns for type of hospital, professional discipline, the hospital's religious affiliation, and self-reported spirituality. Results are discussed in relation to historical views of spirituality and religion within the different disciplines.